Postanowienia Ustawy z dnia 23 marca 2017 r. o kredycie hipotecznym oraz o nadzorze nad pośrednikami kredytu hipotecznego i agentami oraz rekomendacji S Komisji Nadzoru Finansowego a zapobieganie kryzysom bankowości hipotecznej - Fedorowicz, Magdalena (Studia Prawa Publicznego, 2019)
On 23 March 2017, the Act on mortgage credit and supervision of mortgage credit intermediaries and agents was passed, which implements Directive 2014/17/EU of the European Parliament and of the Council of 4 February 2014 on credit agreements for consumers relating to residential immovable property and amending Directives 2008/48/EC and 2013/36/EU and Regulation (EU) No 1093/2010. The Act on mortgage credit under examination contains consumer protection standards for mortgage banking services, which can pursue objectives and perform macro-prudential functions in the ﬁ nancial system. The Act also provides for the supervision of mortgage intermediaries and their agents providing mortgage credit services, rightly considering that since this is a matter of macro-prudential substance and capable of having an impact on ﬁ nancial stability, a comprehensive supervision of the activities of mortgage intermediaries and agents is justiﬁ ed. The aim of the study is to (i) examine the provisions of the Act on mortgage credit from the perspective of its macro-prudential content; (ii) reconstruct this potentially macro-prudential content; (iii) assess the regulatory arrangements for credit intermediaries and residential immovable property agents adopted by the Act; and (iv) address the issue, relevant to the theory of ﬁ nancial market law, of the interference between private and public law rules in terms of their macro-prudential content and macro-prudential policy. It is also intended to perform a comparison of the provisions of the Act on mortgage credit with selected recommendations of Recommendation S of the Financial Supervision in order to assess their macro-prudential nature and the appropriateness of the regulatory solutions adopted by means of an act or by means of national soft banking law to which Recommendation S belongs.